FRAMING OF AFGHAN TALIBAN REGIME IN EDITORIALS OF THE US, INDIAN AND PAKISTANI PRINT MEDIA - Khan, Dr.Rooh ul Ameen; Muhammad Sadam; Dr. Bin Yamin Khan (Journal of Peace, Development and Communication, 2023)
This research examines framing of Taliban regime, that took place on August 15, 2021, in the editorials of Pakistani (Daily Dawn), U.S (The New York times, NYT) and Indian (The Hindu) print media. Editorials of the selected newspaper were collected using ProQuest. The word "Afghanistan Government" is searched and selected from August to November 2021 for the selected newspaper. 20 editorials of NYT predicted 2021 Taliban control where 35% of editorials framed conflict, 30% having responsibility, 20% economics, 10% morals, & 5% framed it as human interest. However, daily Dawn published 17 editorials on the subject of Taliban control over Afghanistan. 35% emphasised economy, 29% mortality, 17% responsibility, 11% human interest, 5% conflict. 11 editorials in The Hindu discussed Taliban control, where 36% emphasised responsibility, 27% economy, and 9% mortality & conflict. Daily Dawn was either neutral or positive however, criticizing the Taliban, a negative tone is used.